2008
DOI: 10.1002/jmv.21326
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hepatitis delta virus (HDV) in Iran: A preliminary report

Abstract: To identify hepatitis delta virus (HDV) genetic variability and its circulating genotypes amongst infected Iranian patients, 25 patients with positive anti-HDV status from different parts of Iran were enrolled in this cross-sectional study. A portion of the HDV delta antigen was amplified, sequenced, and subjected to molecular and phylogenetic analysis. Clinical features and virological markers were evaluated. HDV RNA could be detected in 88% of anti-HDV positive cases (22 patients) with chronic hepatitis B vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
(47 reference statements)
5
10
0
Order By: Relevance
“…The study revealed HDV clade I (genotype 1) in all of the patients. This result is in agreement with predominant genotype of HDV reported in other studies from Iran (18, 38), and also the Middle East region such as Lebanon Egypt, Turkey and Pakistan (17, 35, 39, 40). Previous findings indicated that there may be an association between the geographical distribution of HDV and HBV genotypes (38).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The study revealed HDV clade I (genotype 1) in all of the patients. This result is in agreement with predominant genotype of HDV reported in other studies from Iran (18, 38), and also the Middle East region such as Lebanon Egypt, Turkey and Pakistan (17, 35, 39, 40). Previous findings indicated that there may be an association between the geographical distribution of HDV and HBV genotypes (38).…”
Section: Discussionsupporting
confidence: 93%
“…Genotype ΙΙ is predominant in the Far East (17) and Genotype ΙΙΙ is predominantly detected in South America (3). The predominant genotype of HDV reported from Iran is Genotype Ι (18). Recent extensive analysis of HDV sequences has indicated that the various HDV genotypes fall into at least seven clades (19) and in a study (20) proposed an extended classification of the delta virus genus to eight clades.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of Turkish HDV1-infected samples indicates that S202 is significantly more prevalent in Turkey than in Europe or Asia. The same pattern was also described recently in Iran [29]. Thus, a significant proportion of HDV1 isolates circulating in Turkey (and perhaps Iran) could have evolved from an ancient radiation of an African HDV1 lineage, consistent with the hypothesis that HDV might constitute an efficient marker of human migration [23,38].…”
Section: Discussionsupporting
confidence: 71%
“…Ninety-six articles were found in the literature review, 40 of which [4][10][11][12][13][15][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were potentially related to HDV prevalence in Iran. The detailed search process is demonstrated in Diagram 1.…”
Section: Resultsmentioning
confidence: 99%